Epidemic and Social Isolation: Research on the Tuberculosis Epidemic until the Middle of the 20th Century and Patients’ Social Problems, Treatment and Adaptation - Elena Azmanova-Rudarska (Slavia Meridionalis, 2022)
Epidemic and Social Isolation: Research on the Tuberculosis Epidemic until the Middle of the 20th Century and Patients’ Social Problems, Treatment and Adaptation